Digital factory to support deadlines prediction in small volume production. Issue 10 (2022) - Debevec, M.; Simic, M.; Herakovic, N.
Abstract: Digital production in the digital factory is a modern approach to support the production process. It offers the possibility of achieving continuous progress at the logistical level of the production process in the company. This paper presents an innovative approach of a digital factory for use in SMEs with small volume production. The digital factory is created on this basis and on the real example of a tool shop. With simple settings, the simulation of the defined schedule can be performed quickly and the simulation results can be used to identify potential bottlenecks to create an optimal schedule. The built-in indicators that clearly characterize the state of the production process in the digital factory are also explained, and the progress of each operation on a time scale can be read from the visual printouts.